The Notion of Religion in the Fusus Al-Hikam of Ibn ‘Arabi - Cihan, Ahmet Kamil (Afkar: Jurnal Akidah dan Pemikiran Islam, 2010)
Abstract Ibn ‘Arabi deals with the notion of religion on the basis of a twofold categorization: “the religion with God” and “the religion with people”. While the former refers to the religion revealed by God and promulgated by a prophet, the latter designates the laws and conventions that are developed and enacted by men, possessing no divine origin. However, Ibn ‘Arabi considers the latter to be respectable and valid as long as it is in harmony with the rulings of God in terms of objectives. Ibn ‘Arabi identifies three meanings of the Arabic term “dīn” (usually rendered as “religion”), namely ‘surrender or obedience,’ ‘reward,’ and ‘repetition or custom’. This holds true of both the outer and the inner dimensions of religion. In the context of the outer dimension, the bearers and medium of these meanings are human beings, for they give existence and sustain religion by surrendering, rewarding, and perpetuating the divine messages preached by a prophet. In the inner dimension, the subject of the above meanings is God; for He gives existence and sustains religion by means of Self-manifestation and by rewarding people in accordance with their state. However, by ascribing a role to human will in divine Self-manifestation, Ibn ‘Arabi tries to preserve human freedom.